Bioinspired nanofilament coatings for scale reduction on steel - Siad Dahir Ali; Mette Heidemann Rasmussen; Jacopo Catalano; Christian Husum Frederiksen; Tobias Weidner (Beilstein Journal of Nanotechnology)
Scaling of steel surfaces, prevalent in various industrial applications, results in significant operational inefficiencies and maintenance costs. Inspired by the natural hydrophobicity of springtail (Collembola) skin, which employs micro- and nanostructures to repel water, we investigate the application of silicone nanofilaments (SNFs) as a coating on steel surfaces to mitigate scaling. Silicone nanofilaments, previously successful on polymers, textiles, and glass, are explored for their hydrophobic properties and stability on steel. Our study demonstrates the successful coating of stainless steel with SNFs, achieving super-hydrophobicity and resilience under high shear stress and explosion/decompression tests. Scaling experiments reveal a 75.5% reduction in calcium carbonate deposition on SNF-coated steel surfaces. This reduction is attributed to altered flow dynamics near the super-hydrophobic surface, inhibiting nucleation and growth of scale. Our findings highlight the potential of bioinspired SNF coatings to enhance the performance and longevity of steel surfaces in industrial environments.